2000
DOI: 10.1139/z00-080
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the male intromittent organ of the Trinidadian guppy (Poecilia reticulata)

Abstract: Sexual selection may favour the evolution of elaborated genital traits in males, particularly when phenotypic variation in such traits results in corresponding variation in reproductive success among males in the population. Compared with insects, very little is known about the natural variation in any male genital trait, and its causes, in vertebrates. Here we report on variation in a male intromittent organ both within and between natural populations of a vertebrate, the Trinidadian guppy (Poecilia reticulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 37 publications
8
94
3
Order By: Relevance
“…Interestingly, the pattern observed in the two Gambusia species in the present study is opposite that observed in previous studies of intraspecific divergence in gonopodium size (9,54). In these other studies, males exhibited larger gonopodia in predatory environments compared with low predation localities, indicating that predation's influence on gonopodium diversification may be complicated.…”
Section: Species Yearcontrasting
confidence: 99%
“…Interestingly, the pattern observed in the two Gambusia species in the present study is opposite that observed in previous studies of intraspecific divergence in gonopodium size (9,54). In these other studies, males exhibited larger gonopodia in predatory environments compared with low predation localities, indicating that predation's influence on gonopodium diversification may be complicated.…”
Section: Species Yearcontrasting
confidence: 99%
“…Although this study was criticized on methodological grounds [44], re-analysis did little to change the initial conclusions [45]. Negative genital allometry has subsequently been reported in other species [46], but there are cases of positive genital allometry [47,48]. Nevertheless, if the intromittent organ is generally under stabilizing selection, as appears to be the case [43], it raises the interesting question of how divergence is initiated.…”
Section: Genital Allometry and Variationmentioning
confidence: 84%
“…The average coefficients of phenotypic variation were 5.9% across seven genital traits in the waterstrider G. incognitus (Arnqvist & Thornhill 1998), 8.1% for the length of the gonopodium of Poecilia reticulata (Kelly et al 2000), 10.8% for the length of the gonopodium of Brachyrhaphis episcopi ( Jennions & Kelly 2002) and a mean of 6.5% for a variety of genital traits measured across 20 species of insect and spider (Eberhard et al 1998). Genital traits were at least as variable as general body size, a finding also consistent with Arnqvist & Thornhill's (1998) study of waterstriders.…”
Section: Discussionmentioning
confidence: 99%